Types and styles of painting preferred by a hotel in Malaysia / Khayril Anwar Khairudin ... [et al.] - Khairudin, Khayril Anwar; Abd Rashid, Mohd Sabrizaa; Ab Gani, Muhamad Abdul Aziz; Yahaya, Mohamad Hafiz; Mohd Zamari, Zarlina; Amer Hamzah, Ahmad Fauzi (Universiti Teknologi MARA, Perak, 2022)
Presently, the hospitality industry's development, particularly the hotel industry materialised in Malaysia, has equally improved the nation's art industry. These are a positive development, especially towards arts in Malaysia. Besides being made as a new market for the nation's art industry, it is also a solution for the survival issue among the fresh new artists in Malaysia. To establish the hospitality industry as a new market for the nation's art industry, a study towards the types and the styles of painting is needed. Therefore, the research objectives are to identify the types of painting often purchased by the hotel and analyse the painting styles, which have become the priority for Malaysia's hotel industry. This study was conducted on five selected hotels using a qualitative approach. Besides, this research also applied the exploratory method case study which the researcher act as an observer to assess the paintings purchased by the hotel. The outcome of this research will be made as a guideline,especially for new artists to come up with a type and style of painting that meets the criteria of the hotels in Malaysia. The research also contributes to Malaysia's theoretical arts, considering that there is minimal research like thisin Malaysia before.